Soil Erosion and Sediment Yield of a Sanitary Landfill Site - A Case Study - Oon, Y.W.; Chin, N.J.; Law, P.L (Universiti Malaysia Sarawak, 2011)
This research presents the results of a study on soil erosion rates and sediment yields of a proposed Level 4 Sanitary Landfill construction site located in Sibu, Sarawak. Assessments on potential soil erosion rates and sediment yields during pre-construction, construction and operation stages were carried out using the Revised Universal Soil Loss Equation (RUSLE) and Modified Universal Soil Loss Equation (MUSLE), respectively. It was found that soil erosion rates during construction and operation stages fell under “Moderately High” category, whereby highest sediment yield occurred during construction and operation stages. Comparative analysis on with and without Best Management Practices (BMPs) during construction stage demonstrated that BMPs could significantly reduce the rate of soil erosion, and this sediment yields.